Dataset on industrial waste compositions in West Kazakhstan and conditions for processing them into construction materials - Saule M. Bazarbayeva (Data in Brief, 2024)
The paper presents data on the complex processing of large-tonnage waste from oil and gas industry and chemical production, as well the methods of their utilization and processing.The data was collected at the industrial sites of the plants in Western Kazakhstan.During the work, there were studied data on the chemical composition of the waste, properties of the experimental compositions, material structure, and peculiarities of the technological processes of recycling. When processing the data, there were used such physical-chemical and mechanical methods as X-ray structure, mass and IR spectroscopy, radiometric analysis of the experimental samples. The paper provides data on thermodynamic calculations for chemical reactions of interaction between components of the compositions.It is established that the reaction of interaction of petroleum sulphur with sludge monochromate in the production of polymer concrete significantly reduces their toxicity. On the basis of researching data on the composition and properties of wastes and semi-finished products evidence about the possibility to recycle them into goods with positive ecological and economic effect has been obtained.The given data on practical methods of complex processing and waste recycling (on the example of Western Kazakhstan), allow systematically solving the problem of solid waste management, realizing the basic ecological principle “waste to income” and may be suitable for similar enterprises in other developing countries.